2019
DOI: 10.1111/jce.14251
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh‐density mapping supplemented with global chamber activation identifies noncavotricuspid‐dependent intra‐atrial re‐entry conduction isthmuses in adult congenital heart disease

Abstract: Objective To evaluate the role of ultrahigh‐density mapping for conduction isthmus (CI) characterization in adult congenital heart disease (ACHD). Background Catheter ablation remains suboptimal for ACHD with atypical intra‐atrial reentrant tachycardias (IART) that can be challenging to define using existing mapping technology. Methods An ultrahigh‐density mapping system was selectively employed over a 1‐year period for procedures involving noncavotricuspid isthmus‐dependent‐IART. A global activation histogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 18 publications
10
18
0
Order By: Relevance
“…In our study, 1.7 ATs per patient were detected and mapped. This is in line with previous studies, in which 1.3–1.6 AT forms per patient were reported 9,15,21,22 . The mean CL of our macro re‐entrant AT was 291 ms, which is also comparable to previous studies (CL range from 275 to 299 ms) 15,21 …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, 1.7 ATs per patient were detected and mapped. This is in line with previous studies, in which 1.3–1.6 AT forms per patient were reported 9,15,21,22 . The mean CL of our macro re‐entrant AT was 291 ms, which is also comparable to previous studies (CL range from 275 to 299 ms) 15,21 …”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the results of previous studies, a history of preablation or cardiac surgery was present in most of the studied patients 5,18–20 . Mean age in our study cohort was 71 years, which is rather old compared to patient cohorts of previous studies 9,15,21 . In our study, 1.7 ATs per patient were detected and mapped.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our median ablation time necessary for the acute procedural success of 3.1 min for the non‐CTI group was relatively low, in spite of multiple tachycardias ablated in 14 of 42 procedures. Previous studies in CHD using the Rhythmia System reported a mean procedure ablation time ranging from 14 to 39 min 6,8,10,11,18,21,22 . Despite our short ablation time, there was a low rate of recurrence for the ablated arrhythmias, in particular for the non‐CTI group.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies in CHD using the Rhythmia System reported a mean procedure ablation time ranging from 14 to 39 min. 6,8,10,11,18,21,22 Despite our short ablation time, there was a low rate of recurrence for the ablated arrhythmias, in particular for the non-CTI group. At our repeat procedures, the previously ablated sites or areas of conduction block had remained persistently blocked and the sustainability of our results could be confirmed with other HD mapping systems (Figure S1).…”
Section: Follow-upmentioning
confidence: 86%